TAFSIR AYAT AL QUR’AN TENTANG TUJUAN PENDIDIKAN (QS. ALI IMRAN/3: 138-139 - Ade pratiwi; suci wahyuni; Ramla; Sulkifli; Agus Masykur (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
Islamic education is a comprehensive process of human development aimed at shaping individuals who are faithful, pious, knowledgeable, and possess noble character. Education in Islam does not merely focus on intellectual aspects, but also includes spiritual, moral, and physical development. The purpose of Islamic education is directed toward achieving happiness in both this world and the hereafter, as well as forming the perfect human being (insan kamil). The Qur’an, as the primary source of Islamic teachings, provides guidance concerning the goals, methods, and values of education. Surah Ali Imran verses 138–139 affirm that the Qur’an is a guidance for mankind and that Islamic education should be able to develop individuals who are strong, optimistic, and steadfast in their faith.